2004
DOI: 10.1108/14691930410567013
|View full text |Cite
|
Sign up to set email alerts
|

The role of social capital in today's economy

Abstract: The rapid and well‐known evolution – considered by many observers to be revolutionary – from industrial society to knowledge society, defined by the importance of knowledge creation processes, is showing the relevance of the social capital of organizations. This study seeks to contribute to the development of this new concept. First, presents the theoretical background of social capital. Second, based on an intellectual capital approach, tests the situation of social capital in some Spanish companies, with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(61 citation statements)
references
References 30 publications
0
47
0
4
Order By: Relevance
“…There is no doubt that there are many other important factors that contribute to enhance the performance of organizations but in a knowledge-based economy, many researchers such as (Bataineh & Al Zoabi, 2011;Bontis et al, 2000;Bueno, Salmador, & Rodríguez, 2004;Díez, Ochoa, Prieto, & Santidrián, 2010;Khalique, Shaari, & Isa, 2011;Ordonez de Pablos, 2004) have found that intellectual capital is one of the most important and strategic assets for the success of organizations. They argued that in a competitive business environment intellectual capital is considered as the life blood of knowledge intensive organizations.…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that there are many other important factors that contribute to enhance the performance of organizations but in a knowledge-based economy, many researchers such as (Bataineh & Al Zoabi, 2011;Bontis et al, 2000;Bueno, Salmador, & Rodríguez, 2004;Díez, Ochoa, Prieto, & Santidrián, 2010;Khalique, Shaari, & Isa, 2011;Ordonez de Pablos, 2004) have found that intellectual capital is one of the most important and strategic assets for the success of organizations. They argued that in a competitive business environment intellectual capital is considered as the life blood of knowledge intensive organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned authors state that Intellectual Capital is based on various intangible resources, such as employees' competence, knowledge, education, skill, intellectual agility, brand name, customer relationship and organization structure, taking into consideration that Ismail (2005) added Spiritual Capital as the fourth component of Intellectual Capital [51], and that Bueno, Salvador, and Rodriguez (2004) [52] and Wu and Tsai (2005) [53] had extended the concept of Intellectual Capital in their research and introduced two more components, namely Social Capital and Technological Capital. However, Ramezan (2011) states that the components of Intellectual Capital are Human Capital, Organizational Capital (or Structural Capital), Technological Capital, Social Capital and Business Process Capital (or Customer Capital) [54].…”
Section: Process and Componentsmentioning
confidence: 99%
“…The analysis of both training and ACAP can be performed based on resource-based theory (Barney 1991; Grant 1996; Sveiby 1997; Wernerfelt 1984), knowledge management (Kogut and Zander 1992; Nonaka and Takeuchi 1995), intellectual capital (Bueno et al 2004; Bontis 2001) and the dynamic capabilities approach (Easterby-Smith and Prieto 2008; Teece et al 1997). This paper aims to integrate them to adequately conceptualize both training and ACAP.…”
Section: Introductionmentioning
confidence: 99%